EKSISTENSI KONSELOR SEBAGAI KHALIFAH PERSPEKTIF TAFSIR MAUDHU'IY - Tri Putri Amelia S; Irman Irman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to examine the existence of counselors as caliphs based on the perspective of maudhu'iy interpretation. The existence of counselors as a profession is considered to have a duty that must be carried out in Islamic da'wah. The task in question is as a caliph on earth. The study of these verses uses the maudhu'iy interpretation method or thematic interpretation. Tafsir maudhu'iy is an interpretation that collects and examines verses on similar themes or issues. In this study focused on the topic of the verses of the AlQuran relating to the caliph and its relation to the existence of counselors. This research is a library research which aims to collect bibliographical data to solve a critical and in-depth study of relevant library materials. Data collection techniques use documentation methods, such as: books, e-books, journal articles, etc. The data analysis technique used is content analysis, namely by selecting, comparing, combining, sorting out various meanings, until relevant data is found. The conclusion is that counselors must equip themselves with knowledge and reflect the personality of the Islamic counselor. In addition to the provision of knowledge, the counselor as caliph is also characterized by faith and charity, making decisions with the truth and not following desires, and inviting to amar ma’ruf nahi munkar.